Why university students choose an international education: A case study in Malaysia - Pyvis, David; Chapman, A. (Elsevier, 2007)
Why has Australian offshore higher education become the educational investment of choice for many students? What benefits do students anticipate from this education? What is the relationship between educational goals and educational experience? To address these questions, this paper draws on findings from empirical research conducted with students studying at an offshore campus of an Australian university in Malaysia. It was found that students typically chose to enroll with the Australian university to receive an international education. Reasons offered for seeking an international education effectively delineated two groups of students. For Malaysian nationals, an international education was valued largely as a passport to employment with (Western) multinational corporations operating in Malaysia. Generally the Malaysian students made positional investments in Australian offshore higher education. For non-Malaysian students an international education was typically selected as an aid to procuring a new identity. These students chose an international education with the hope of expunging provincial outlooks. From international education, they wanted new ways of viewing the world, new habits of thinking and new skills and approaches. They sought a personal metamorphosis. These students, therefore, typically made self-transformative investments in international education. The paper further shows that investment choices influenced the way students experienced their education. Of the two populations distinguished by investment type, students who made self-transformative investments were more likely to respond positively to challenging education experiences associated with studying at the campus.